Mengapa Masyarakat Memilih Menunaikan Zakat di Masjid Dibandingkan Dengan Lembaga Zakat? (Studi Kasus Pada Masyarakat Desa Kramat Jegu Kecamatan Taman Kabupaten Sidoarjo) - Henry Reza Novianto; Muhammad Nafik HR (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
The purpose of research is to find out Why Public Choose Paying Zakat in Mosque Rather than Institute of Zakat in Kramat Jegu Village.The research methodology used was a qualitative approach, the case study strategy. Data was collected by interviewing nine muzakki zakat payers in Kramat Jegu village Taman sub-disctric who four of them are related to the management of the mosque.The technique used is descriptive analysis.The result showed that the public would prefer to pay zakat in the mosque than zakat institutions. The motivation of public to pay Zakat at mosques fortified with three reasons are take into account the distance of the place of payment of zakat, more public believe to staff management mosque of zakat, and the public awareness to help the surrounding community. REFERENCESAl-Asqolani, Ibnu Hajar. 1996. Tarjamah Bulughul Maram. Bandung: CV. Dipenegoro.Hafidhuddin, Didin. 2002. Zakat Dalam Perekonomian Modern. Jakarta: Gema Insani Press.Karim, H. A. Syafi’i. 2006, Ushul Fiqih. Bandung: CV. Pustaka Setia.Katsir, Ibnu. 1990. Tafsir al-Qur’an alAdzim. Kairo: Darr Kutb.Mahmud Aziz Siregar, Islam Untuk Berbagai Aspek Kehidupan, Tiara Wacana Yogya, Jogjakarta, 1999Nawawi, Ismail. 2010. Zakat Dalam Perspektif Fiqh, Sosial Dan Ekonomi. Surabaya: Putra Media Nusantara.P3EI. 2008. Ekonomi Islam. Rajawali Press: JakartaQardhowi, Yusuf. 1999. Hukum Zakat. Jakarta: PT Pustaka Litera Antar Nusa.-----------------------. 2005. Spektrum Zakat Dalam Membangun Ekonomi Kerakyatan. Jakarta : Zikrul HakimQur’an in Word Ver 1.3 created by Mohammad Taufiq.Pusat Pengkajian dan Pengembangan Ekonomi Islam (P3EI). 2008. Ekonomi Islam. Jakarta: PT Raja Grafindo Persada.Riyandono, Muhammad Nafik Hadi. 2008. Ekonomi ZISWAQ (Zakat Infaq, Shadaqah, dan Wakaf). Surabaya: IFDI dan Cenforis.Ash-Shiddieqy, 2009. Pedoman Zakat. Semarang: PT. PUSTAKA RIZKI PUTRA.Sugiyono. 2010. Memahami Penelitian Kualitatif. Bandung: Alfabeta.Suwandi, & Basrowi. 2008. Memahami Penelitian Kualitatif. Jakarta: Rineka Cipta.Tandika, Didik. 2011. Analisis Faktor-Faktor yang Mempengaruhi Kinerja Organisasi Pengelola Zakat di Propinsi Jawa Barat dan DKI Jakarta. Makalah Call for Paper Up date Ekonomi Akuntansi dan Bisnis1980. Al-Qur’an Secara Lafzhiyah Jilid II. Jakarta: CV. Tri Burnama Utama.2011. Al-Qur’an. Jakarta: Darul Marifah. 2011. Mahfudzhat.2011. Jakarta Selatan: PT. Rene Asia publika.2012. Undang-Undang Pengelolaan Zakat Dan Wakaf. Bandung: Fokus Media